Behavior Study of The Prevention of Covid-19 Transmission with Health Protocol at Transportation Service Office - Nurna Ningsih; Hartati Bahar; Fikki Prasetya (MIRACLE Journal Of Public Health, 2021)
The initial entry of Covid-19 in Muna was 8 cases with the highest number of cases in Southeast Sulawesi. This study aims to determine the behavior of preventing Covid-19 by implementing health protocols at the Transportation Service Office based on the theory of the health belief model. This study uses a qualitative design with a phenomenological approach. Data collected through in-depth interviews, observation and documentation. The results based on the Perceived suspectibility factor informants know that people who are susceptible to Covid-19 are people who are old, people who work in community services. Based on Perceived saverity, the informant said that Covid-19 is a pandemic so it is dangerous because of its transmission, and if infected with Covid-19 it can worsen the condition of people who have congenital diseases. Based on Perceived benefits, informants feel the perceived benefits of implementing health protocols in addition to preventing Covid-19 are also useful for daily life. For Perceived barriers, informants feel obstacles in implementing health protocols such as the use of masks because of the small amount of air they breathe. Meanwhile, the Threat factor, informants feel that when they do not apply the health protocol, they feel afraid or anxious. Self-efficacy informants feel confident in carrying out health protocols because they feel safe. Conclusions based on the theory of health belief model, it is concluded that perceived vulnerability factors, perceived benefits, perceived barriers, threats and self-efficacy indicate the behavior of implementing health protocols at the Transportation Service Office in preventing Covid-19.